Cellular therapies in kidney transplantation. Issue 6 (November 2021) - Leclerc, Simon; Lamarche, Caroline
Abstract : Purpose of review: Current immunosuppressive regimens used in kidney transplantation are sometimes ineffective and carry significant risks of morbidity and mortality. Cellular therapies are a promising alternative to prolong graft survival while minimizing treatment toxicity. We review the recently published breakthrough studies using cell therapies in kidney transplantation. Recent findings: The reviewed phase I and II trials showed that cell therapies are feasible and safe in kidney transplantation, sometimes associated with less infectious complications than traditional regimens. Regulatory T cells and macrophages were added to the induction regimen, allowing for lower immunosuppressive drug doses without higher rejection risk. Regulatory T cells are also a treatment for subclinical rejection on the 6 months biopsy. Other strategies, like bone marrow-derived mesenchymal cells, genetically modified regulatory T cells, and chimerism-based tolerance are also really promising. In addition, to improve graft tolerance, cell therapy could be used to prevent or treat viral infection after transplantation. Summary: Emerging data underline that cell therapy is a feasible and safe treatment in kidney transplantation. Although the evidence points to a benefit for transplant recipients, studies with standardized protocols, representative control groups, and longer follow-up are needed to answer the question definitively and guide future research.